Sosialisasi Strategi Pemasaran Modern Bagi Pelaku Usaha Kecil Menengah Produk Makanan Berbahan Dasar Singkong di Kelurahan Blooto Kota Mojokerto - Rachmad Sholeh; Setyaasih Setyaasih; Fajar Budiyanto; Sugeng Eko Yuli Waluyo (Fakultas Teknik Universitas Cenderawasih, 2023)
The abundance of crops, especially cassava in the Blooto sub-district, has made many people sell processed food products made from cassava. However, due to a lack of information about marketing strategies, SMEs products from the Blooto sub-district can only be sold in the local market. Even then, they must compete with products from outside which are the result of large-scale industrial factories with well-known brands. This community service report tries to provide the best solution on modern digital marketing promotion strategies by utilizing social media to help SMEs market their products so they can penetrate regional, national and even foreign markets. Of course this is also balanced with attractive product innovations as well as support from the government as regulatory policy makers.